FORMULASI BUBUR INSTAN MENGGUNAKAN KOMPOSIT TEPUNG KACANG MERAH DAN PATI GANYONG SEBAGAI MAKANAN SAPIHAN - Yustiyani Yustiyani; Budi Setiawan (Jurnal Gizi dan Pangan, 2013)
The purpose of this study was to formulate instant baby porridge as a source of protein weaning food based on red beans flour and canna starch composite. The design of this study was a complete randomized design with one factor which was the ratio of red beans flour and canna starch in composite composition as instant porridge ingredient (2:1, 3:1, and 4:1). Based on organoleptic test, F2 which used red bean flour and starch canna ratio by 3:1 was the best formula. The optimal time to brew the instant porridge was 62 seconds with amount of water used was 3 ml/g. The instant porridge bulk density was 0.61 g/ml and water absorption was 4.67g/g. This instant porridge contained 363 kcal/100 g, 16.57% protein, 1.48% fat, 70.84% total carbohydrate, 197.70 mg calcium, 8.17 mg zinc, and 16.48 mg iron. Protein digestibility of this porridge was 79.83%. As per 27 g serving size of this instant porridge can fulfill 22.25% protein, 55.25% iron, 27.63% zinc so that it can be claimed as food source of protein and zinc, and high iron.